TEORICAL STUDY AND COMPUTACIONAL DESING OF STRUCTURAL BIOLOGICAL ACTIVITY OF DRUGS (Jóvenes en la Ciencia, 2015)
Drug design is the process through which it is proposed a new molecule with possible pharmacological activity. This process is carried out mainly in two ways: from the knowledge of the structure of the ligand (like a lead drug) or from knowing the structure of the receptor (Biological target). In this project we are proposing a QSAR model, we perform geometry optimization and calculate meaningful quantum mechanics parameters of a family of quinolones and their derivatives, with clinical importance as antibiotic agents, through theoretical and computational chemistry methods, using the Gaussian 09 package. Furthermore we are proposing a correlation between electronic and geometrical properties with the medium inhibitory concentration (Experimental MIC), from a study of Quantitative Structure Activity Relationship (QSAR). The last lap of this work consist in understanding the mechanism of bacterial grow inhibition, using Docking methodologies. As results, we are proposing two QSAR models for a selected family of quinolones and we propose three new compounds as possible antibiotic agents, this last resulting with a better predicted “theoretical” activity than the selected family of quinolones. Also, we obtain the stacking interactions, face-to-face, between the quinolone and DNA rings, which are key in the action mechanism of this kind of drugs.